Effect of strain due to Ni substitution in CeO2 nanoparticles on optical and mechanical properties. (1st March 2017) - Tiwari, Saurabh; Bajpai, Gaurav; Srivastava, Tulika; Viswakarma, Srashti; Shirage, Parasharam; Sen, Somaditya; Biring, Sajal
Abstract: CeO2, a strong cubic fluorite structured ceramic, with well-defined optical and mechanical properties may be modified by proper substitution. Ni substitution in Ce1 − x Nix O2 (0 ≤ x ≤ 0.08) nanoparticles, hints at strain generation in the lattice bringing in changes in structural properties. The strain introduces changes in the electronic, optical and mechanical properties. The origin of strain is discussed using structural, optoelectronic, vibrational and mechanical studies discussing the elastic and plastic behavior of the materials. Graphical abstract: